2015
DOI: 10.2308/accr-51148
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Incentives, Feedback, and Recognition—Complements or Substitutes? Evidence from a Field Experiment in a Retail Services Company

Abstract: This study investigates the performance effects of the combined use of three reinforcers, or incentive motivators, commonly used by companies: monetary incentives, feedback, and recognition. Using a field experiment in a retail services company, I test whether these incentives, which appeal to diverse motivation mechanisms—tangible payoffs, self-regulation, and social esteem—and, hence, have different utilities, are complements or substitutes. The results of the hard performance data collected, in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 57 publications
3
22
0
4
Order By: Relevance
“…There is a strand of literature in organizational psychology, however, that argues that monetary incentives do not work well in combination with recognition . This is in line with Lourenço () who finds in her field experiment with sales representatives that money and recognition (via awards) are substitutes. Both have a positive effect on performance when applied in isolation but the joint effect is not statistically distinguishable from the effect of money or recognition alone.…”
Section: Literaturesupporting
confidence: 85%
“…There is a strand of literature in organizational psychology, however, that argues that monetary incentives do not work well in combination with recognition . This is in line with Lourenço () who finds in her field experiment with sales representatives that money and recognition (via awards) are substitutes. Both have a positive effect on performance when applied in isolation but the joint effect is not statistically distinguishable from the effect of money or recognition alone.…”
Section: Literaturesupporting
confidence: 85%
“…Finance scholars have found that CEOs are willing to trade off social status from working for a publicly admired company (Focke, Maug, & Niessen-Ruenzi, 2017) or being awarded member of an order of merit (Siming, 2016) against additional monetary compensation. In accounting, advancements suggest that the combined used of nonmonetary and monetary incentives can produce a substitution effect (Lourenço, 2016). Strategy scholars have addressed how nonmonetary awards in corporations can be used strategically; for instance, using them to compensate prosocial behaviors and signal to employees that the firm values collaboration (Gallus & Frey, 2017).…”
Section: N O T E Smentioning
confidence: 99%
“…Stajkovic and Luthans () present a meta‐analysis of behavioral management studies, analyzing if and how different rewards (money, social recognition, and feedback) interact with one another. Similarly, Lourençco () reports the findings from a field experiment with retail sales representatives that looks at interaction effects among this same set of motivators (money, recognition, and feedback). Kvaloy, Nieken, and Schöttner () find that the effectiveness of piece rates interacts with motivational talk, and Bradler and Neckermann () show that gifts that combine recognition and money only work well when they come with a personal touch.…”
mentioning
confidence: 99%